OPTIMIZATION OF PROCESS PARAMETERS FOR PSEUDOMONAS DIMINUTA, P. PUTIDA AND P. AERUGINOSA FOR BIODEGRADATION OF METHYL PARATHION - JYOTI SHARMA; A.K. GOEL; K.C. GUPTA (International Journal of Pharma and Bio Sciences, 2014)
Pseudomonas diminuta, P. putida and P. aeruginosa were established as a biodegrading agent for Methyl Parathion (MP) at 1200 mg/L, under basic growth parameters for mesophiles. In this study, the effects of process parameters, such as temperature, pH, salinity, carbon and nitrogen sources on the growth of those bacteria were studied and optimized to establish higher degradation of the target chemical. The growth was assessed in BMM containing MP at various temperatures such as 25°C, 30°C, 37°C and 40°C; at various pH such as 7.0, 8.0, 8.5, 9.0 and 9.5; at various salinity such as 0.1%, 0.5%, 1%, 2.0% and 3.5%; and glucose (1 gm/L) and yeast extract (0.5 gm/L) separately. The higher growth was recorded at 37°C and pH 8.5. Salinity and addition of supplements did not support the bacterial growth. These species may be used to treat MP polluted soils by providing optimized conditions suggested by the present study